Alimentação de espécies onívoras dominantes na comunidade de peixes na área de influência da usina hidrelétrica de estreito: Rio Tocantins, MA - Alves, Adriana Martins da Rocha Maués (2012)
The industrial development associated to population higher contributes to increase water and energy consumption. The rivers impoundment is one of alternatives used to attend this growing consumption. Studies realized in artificial impoundments show also direct alterations in abundance and ichthyofauna diversity, despite some species adapt better in new conditions, incrementing your abundance, others can reduce it, displaced to others regions or extinct. The objective of this work is determinate the diet of the more abundant omnivorous species in communities, under the direct influence of Estreito´s Hydroelectric, in Tocantins River, Maranhão, Brazil, also checking the diet changes in these species, between hydrologic periods and river phases. The fishes were collected in November 2009 to October 2010 (river), and November 2010 to April 2011 (filling). We analyzed stomachic content of eight species, totaling 1188 specimens, 791 in the river phases (494 in rain period and 297 in dry period) and 397 of filling phase. We were utilized two analysis methods: occurrence frequency and relative volume, combined in the Alimentary Index. Multivariate analysis was realized to detect changes in diet between the periods of hydrologic cycle and reservatory phases. All species were confirmed as omnivorous, in some cases showing tendencies to herbivore or carnivore. Little differences were evidenced between reservoir periods and phases, including some changes in feed preferences caused by increased availability of resources in rainy season and the stage of reservoir filling. The results confirm that changes in diet due to impoundments must be accompanied, because they may be responsible for changes in fishes community after impoundment.